The mighty Thor. Vol. 1, Thunder in her veins - Aaron, Jason (Marvel Enterprises, 2016)
"When Dr. Jane Foster lifts the mystic hammer Mjolnir, she is transformed into the Goddess of Thunder, the Mighty Thor! Her enemies are many, as Asgard descends further into chaos and unrest threatens to spread throughout the Ten Realms. Yet her greatest battle is against a far more personal foe: the cancer that is killing her mortal form. When Loki steps back into Thor's life, will it ease her troubles or only add to her pain? It's time to find out whether the next chapter in the twisting tale of the Trickster will be one of good or evil! There's no such question about Malekith, though, as he and his Dark Council continue to fan the flames of a looming War of Realms! Jason Aaron continues his startling saga of the mighty Thor!"--Amazon.